2022
DOI: 10.1002/mde.3777
|View full text |Cite
|
Sign up to set email alerts
|

Social performance versus relative performance evaluation, asymmetric costs, and quantity competition under managerial delegation

Abstract: This paper considers asymmetric performance evaluation measures in a duopoly with asymmetric costs and managerial delegation under quantity competition. Asymmetry along performance measures as well as cost leads to a several surprising results. First, we find that the social performance firm with a cost advantage earns a larger profit than its rival under a specific economic environment. Second, when the relative performance firm has the cost advantage, both firms adopt a less aggressive strategy under specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Following Aggarwal and Samwick (1999) and Fumas (1992), previous studies have considered the impact of RPEs on firm strategies or social welfare based on a managerial delegation game (e.g., Asseburg & Hofmann, 2010; Chirco et al., 2011; Hamamura & Ramani, 2023; Hattori & Tanaka, 2016; Huang et al., 2020; Matsumura et al., 2013; Miller & Pazgal, 2005; Satoh & Tanaka, 2014; Tanaka, 2014; Wu, 2012; Xu & Matsumura, 2022).…”
Section: Related Literaturementioning
confidence: 99%
“…Following Aggarwal and Samwick (1999) and Fumas (1992), previous studies have considered the impact of RPEs on firm strategies or social welfare based on a managerial delegation game (e.g., Asseburg & Hofmann, 2010; Chirco et al., 2011; Hamamura & Ramani, 2023; Hattori & Tanaka, 2016; Huang et al., 2020; Matsumura et al., 2013; Miller & Pazgal, 2005; Satoh & Tanaka, 2014; Tanaka, 2014; Wu, 2012; Xu & Matsumura, 2022).…”
Section: Related Literaturementioning
confidence: 99%
“…Under the vertical market structure, Wang (2023a) found that managerial delegation can increase downstream firm profits. Existing literatures have analyzed the effect of production costs (Fanti & Meccheri, 2017; Hamamura & Ramani, 2023), horizontal shareholding (Nakamura, 2011), overinvestment (Pal, 2010), R&D spillover (Kräkel, 2004), corporate social responsibility (Fanti & Buccella, 2019), product quality (Wang & Wang, 2021), and market competition (Nakamura, 2017) on managerial delegation contracts. Privatization is an important part of government decision‐making (Chen et al, 2023), and there are also studies that analyze the impact of privatization decisions on management authorization contracts (Tomaru et al, 2011).…”
Section: Introductionmentioning
confidence: 99%